Project Based-Learning and Creativity : Is the Application of Project-Based Learning Can Increase Student Creativity in Making Learning Videos? - Yahya Eko Nopiyanto; Arwin (Jurnal Pendidikan Kesehatan Rekreasi, 2023)
Student creativity is one of the skills needed by students to succeed in a learning process. however, unfortunately, it is still often ignored by lecturers when in the learning process. Therefore, one of the efforts to increase student creativity is to apply the right learning model. In this study, the goal to be achieved is to increase the creativity of physical education students in making learning videos. The method applied is classroom action research. Based on the results of observations in cycle 1, it is known that students get an average score of 65%, and in cycle 2 of 82,5%. the results of the product assessment showed that in the first cycle the students got an average score of 70 and in the second cycle 82,5. It can be concluded that the application of project-based learning can increase student creativity in making learning videos in athletic learning courses.